2017
DOI: 10.1371/journal.pone.0172118
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lightning induced voltage on the distribution power line polymer insulators

Abstract: Protection of medium voltage (MV) overhead lines against the indirect effects of lightning is an important issue in Malaysia and other tropical countries. Protection of these lines against the indirect effects of lightning is a major concern and can be improved by several ways. The choice of insulator to be used for instance, between the glass, ceramic or polymer, can help to improve the line performance from the perspective of increasing the breakdown strength. In this paper, the electrical performance of a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This challenges the range of the wireless network. In these setups, wiring the sensors together is often not an option because of the installation complexity and operational hazards [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This challenges the range of the wireless network. In these setups, wiring the sensors together is often not an option because of the installation complexity and operational hazards [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, electric brackets and leaks will appear on the insulator [10]. Most of the previous research that was based on it shows that the excess voltage in the lightning is considered one of the main factors that cause annular flash and damage to the insulators in the transmission lines [11,12]. The previous studies were taken to effect the grounding resistance by metal-oxide gapless surge arresters and the obtained results indicate the possibility of reducing the effects of lightning according to the mechanism of the lightning rod dependent to some case [13].…”
Section: Introductionmentioning
confidence: 99%
“…The direct effects are related to the direct interaction with insulators, while indirect effects are caused by transient HV pulses induced in other power network components such as power lines. Studies in this direction were carried out; for example, for 10 kV polymer insulators under different conditions for impulse, weather and insulator angle with respect to a cross-arm [31]. The results showed that the weather and insulator angle (with respect to the cross-arm) have a dominant influence on the values of breakdown voltage and leakage current for both negative and positive impulses.…”
Section: Introductionmentioning
confidence: 99%